2017
DOI: 10.1038/s41598-017-16441-y
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of YAP by ARF Stimulated with Tea-derived Carbon Nanodots

Abstract: YAP is a downstream nuclear transcription factor of Hippo pathway which plays an essential role in development, cell growth, organ size and homeostasis. It was previously identified that elevation of YAP in genomics of genetic engineered mouse (GEM) model of prostate cancer is associated with Pten/Trp53 inactivation and ARF elevation hypothesizing the essential crosstalk of AKT/mTOR/YAP with ARF in prostate cancer. However, the detailed function and trafficking of YAP in cancer cells remains unclear. Using GEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…For instance, C‐dots synthesized from ginger inhibit HepG2 cells growth in vivo of mouse model . C‐dots derived from green tea inhibit the growth of MCF‐7, MDAMB‐231 breast cancers, and prostate cancer cells as we and others showed . C‐dots derived from date pits ( Phoenix dactylifera ) inhibit cancerous cell migration with changes in cytoskeleton .…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…For instance, C‐dots synthesized from ginger inhibit HepG2 cells growth in vivo of mouse model . C‐dots derived from green tea inhibit the growth of MCF‐7, MDAMB‐231 breast cancers, and prostate cancer cells as we and others showed . C‐dots derived from date pits ( Phoenix dactylifera ) inhibit cancerous cell migration with changes in cytoskeleton .…”
Section: Introductionmentioning
confidence: 58%
“…C‐dots derived from date pits ( Phoenix dactylifera ) inhibit cancerous cell migration with changes in cytoskeleton . Mechanistically, tea derived C‐dots were found to inhibit cancer cell growth and interact with nuclear protein ARF and regulate hippo pathway . As regular therapies may easily induce drug resistance, there is a huge demand for an alternative approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our recent findings on MMP family protein evolution and translocation, more studies are needed to elucidate both NLMP and disease evolutions [62]. Recently we found YAP is also a shuttling protein localized in cytosol, nucleus and membrane and is regulated by nuclear protein ARF [63]. In addition, MMP nuclear localization correlates to ARF elevation in prostate cancer cells [64].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, carbon dots prepared from a spice have been found to be able to inhibit tumor growth in a xenograft model (17). Another study found that carbon dots prepared from tea can bind to certain amino acids on ARF and colocalize with ARF in the nucleus, thus sensitizing cancer cells to rapamycin (18,19). The current study used an atomic carbon material (Australian patent number: 2005230336, Figure 1).…”
Section: Introductionmentioning
confidence: 99%